Impact of Radiation on Brain Histology of Mice and Rats (Mus musculus and Rattus norvegicus ): A Literature Review : Dampak Radiasi pada Histologi Otak Mencit dan Tikus (Mus musculus dan Rattus norvegicus ): Literatur Review - Sulaeman, Nabila; Febrianti, Liza; Atifah, Yusni; Pratama, Sandi Fransisco; Achyar, Afifatul (Microbiotech, 2024)
Aim This review article is to review and summarize the results of research on the effects of electromagnetic radiation on the brain histology of mice (Mus musculus). Methods This study used a systematic literature review following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data were obtained from articles in PubMed, ScienceDirect, and Google Scholar that met the inclusion criteria: discussing the effects of radiation on the brains of rats and mice, published within the last 10 years, and using experimental methods. A total of 11 selected articles were qualitatively analyzed to evaluate neuronal damage and structural changes in the hippocampus. Results showed that exposure to electromagnetic radiation (EMF) caused histological changes in the brains of mice and rats, such as dilation of the interstitium, interstitial edema, neurodegeneration, and an increase in the number of glial cells. Prenatal exposure reduced brain volume, increased ventricular volume and affected motor activity of rats. Neuronal damage, vacuolization, and structural changes in glial cells and pyramidal neurons indicated the long-term impact of radiation on brain tissue. Main conclusions Exposure to electromagnetic radiation can cause structural damage to neurons and glial cells, such as oedema, apoptosis and neurodegeneration. These findings emphasize the need for further research into the biological mechanisms and health risks of radiation, as well as the development of guidelines to prevent overexposure due to the increasing use of radiation technology. Key words radiation, electromagnetic, brain, neurons, hematoxylin